The Influence of Learning Motivation on Student Achievement in Elementary School - Erick Marantika; Invites Ruslan Wahyudin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This study aims to find out what learning motivation is, how to motivate children to learn, the function of learning motivation at school. The data collection technique is through this research using a qualitative approach, so that the main instrument in this research is the researcher himself. The instruments used in collecting data in the field are in accordance with the object of this journal, by observing and interviewing. The child's educational parenting style must be in accordance with the child's psychological condition, namely with an authoritative style. Second: educating with an Islamic educational perspective, will make children mentally healthier, namely those who have excellent physical condition, high intellectual mental intelligence (IQ), mental health/personality conditions that are mature and stable in their mental-emotional (EQ) have personality integrity high (mental-social) and have firmness of faith and Islam. Third: The important role of psychology in Islamic education is to bridge the process of imparting knowledge so that it pays more attention to the psychology of each individual child or student, because this greatly determines the success of parents or educators in transferring the knowledge given to their children.